ìКОЗАЦЬКАî СЕМАНТИКА ДЕЯКИХ ВЛАСНИХ ГЕОГРАФІЧНИХ НАЗВ УКРАЇНИ: НА МАТЕРІАЛІ УКРАЇНСЬКИХ ПРИСЛІВíЇВ ТА ПРИКАЗОК (Zaporizhzhia Historical Review, 2021)
This article is devoted to research of semantics of proper name in structure of proverbs and sayings, revealing ethnoculture of features of Ukrainian associative thinking. Attempt in particular is made to define semantic majorants in value toponyms, which became symbols Cossack of the period of a history, symbols freedom-loving of our people.